Case report: Rare epithelioid hemangioendothelioma occurs in both main bronchus and lung - Gong, Jiuyu; Tian, Fangfang; Wang, Qin; Mu, Mi; Geng, Sijia; Hao, Pengfei; Zhong, Pengfei; Zhang, Rui; Jiang, Lin; Wang, Rentao; Bao, Pengtao (Frontiers in Medicine, 2022)
Pulmonary epithelioid hemangioendothelioma (PEH) is a rare vascular tumor of endothelial origin with low- to intermediate-grade malignant potential. As there is no characteristic clinical or biological marker for PEH, most cases require a surgical lung biopsy for diagnosis. Until now, although some PEH patients reported in the literature established through bronchoscopic biopsy, most of whom still underwent surgical lung biopsy for confirmation. Here we report on a rare case diagnosed as PEH through endobronchial biopsies to the presence of an intraluminal mass that blocked the trachea and caused atelectasis in the right upper lobe. Moreover, since surgery was not appropriate for this patient with unresectable bilateral multiple nodules, we adopted genetic analysis using NSG to provide a guide for personalized treatment. Then, based on the NGS results, the patient was treated with anti-PD-1 mAb and sirolimus for one year and has been stable in a one-year follow-up examination.